Mandatory Disclosure of SAK ETAP in Mimetic and Normative Isomorphism Perspective on Real Sector Cooperatives In Indonesia - Sartono Sartono; Djoko Suhardjanto; Agung Nur Probohudono; Djuminah Djuminah (Green Publisher Indonesia, 2022)
This study aims to analyze the effect of Institutional Isomorphism on mandatory disclosure with Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The level of mandatory disclosures, measured by an unweighted of 88 disclosure items. The results of the study on 195 real sector cooperatives showed that the level of mandatory disclosure is 31.4%, the highest is 59.4%, and the lowest is 7.5%. Multiple regression analysis shows that information technology, audit types, and entity size, have a significant effect on Mandatory Disclosure of SAK ETAP, while industry types have an moderat significant effect. The theoretical contribution is to provide insight into the use of mimetic and normative isomorphism in explaining mandatory disclosures, while stakeholders can provide input for considering policy and decision making regarding the implementation of financial reporting based on SAK ETAP